Novel thickening agent for oil well fracturing and preparation method thereof
By using monomer dynamic bond design, gradient polymerization function distribution and montmorillonite interface collaborative enhancement in thickening agent for oil well fracturing, the limitations of thickening agent in salt resistance, temperature resistance and self-repair performance are solved, and an efficient and economical oil well fracturing effect is achieved.
Patent Information
- Application Number
- CN202510322166.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
The existing thickeners for oil well fracturing have limitations in their salt resistance, temperature resistance and self-repair performance, and it is difficult to meet the actual needs of complex reservoir conditions.
Through functional coordination and structural design at the molecular level, a new type of thickening agent was developed, using monomer dynamic bond design, gradient polymerization functional distribution and montmorillonite interface coordinated enhancement, forming a closed loop of "salt-temperature resistance-self-healing" performance.
It significantly improves the comprehensive performance of the thickener, maintains stable viscosity in high-mineralization formations, and achieves self-healing under high temperature environments, improving the efficiency and economic benefits of oil well fracturing operations.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thickeners, and in particular to a novel thickener for oil well fracturing and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand, the development of oil and gas resources has gradually expanded to deep sea, deep layer and unconventional oil and gas reservoirs. Under these complex reservoir conditions, oil well fracturing technology has become one of the key means to improve oil and gas recovery. As an important component of fracturing fluid, the performance of thickener directly affects the effect and economic benefits of fracturing operations. However, existing thickeners still have some limitations in practical applications, especially in terms of salt resistance, temperature resistance and self-healing performance.
[0003] In terms of salt resistance, the mineralization of oil well formation water is usually high, containing a large number of salt ions, which will interact with the functional groups in the thickener molecules, causing the viscosity of the thickener to decrease or even fail. For example, traditional polyacrylamide thickeners are prone to salt precipitation in high-salt environments and lose their thickening effect. Although some modified polyacrylamide and supramolecular thickeners have improved salt resistance by introducing hydrophobic groups or supramolecular structures, they still have problems such as high cost and poor solubility.
[0004] In terms of temperature resistance, the temperature of deep oil wells is usually high, requiring the thickener to maintain stable viscosity and structure under high temperature conditions. However, many traditional thickeners are prone to degradation under high temperature conditions, resulting in decreased viscosity and performance degradation. For example, some polyacrylamide-based thickeners will break their molecular chains and lose their thickening ability under high temperature environments above 150°C. Although some new high-temperature resistant thickeners have improved their temperature resistance by introducing high-temperature resistant monomers and cross-linking agents, they still have the problem of insufficient shear resistance.
[0005] In terms of self-repairing performance, the thickener will be subjected to high-speed shear and mechanical wear during the fracturing process, resulting in damage to its structure and decreased viscosity. Although some supramolecular thickeners have achieved self-repairing functions by introducing dynamic bonds, they still have problems such as low repair efficiency in practical applications. In addition, the self-repairing performance of some self-repairing thickeners will also be limited in high temperature and high salt environments.
[0006] In summary, the existing thickeners for oil well fracturing still have certain limitations in terms of salt resistance, temperature resistance and self-repairing performance, and it is difficult to meet the actual needs under complex reservoir conditions. Therefore, the development of a new thickener with excellent salt resistance, temperature resistance and self-repairing performance is of great significance for improving the efficiency and economic benefits of oil well fracturing operations. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a new type of thickener for oil well fracturing.
[0008] A method for preparing a novel thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, hydroxyethyl methacrylate and phenylboric acid are added to ethanol, sealed, stirred, cooled, and distilled under reduced pressure to obtain modified hydroxyethyl methacrylate; S2, dissolving a four-arm polyethylene glycol chain transfer agent, modified hydroxyethyl methacrylate, acrylamide, and hydroxyethyl methacrylate in deionized water, stirring at a constant temperature of 48-52° C. for 1.8-2.2 h, with a stirring speed of 480-520 rpm, adding ammonium persulfate, stirring at a constant temperature of 58-62° C. for 2.8-3.2 h, with a stirring speed of 280-320 rpm, adding ammonium persulfate, stirring at a constant temperature of 68-72° C. for 0.8-1.2 h, with a stirring speed of 180-220 rpm, adding ammonium persulfate, adding hydroquinone, cooling, filtering, and obtaining a gradient branched polymer solution; S3, adding montmorillonite and 3-aminopropyltriethoxysilane to ethanol, sealing, stirring, adding sulfosuccinic anhydride, stirring, adjusting the pH value of the system to 7.2-7.8, adding phenylboric acid, stirring, centrifuging, washing, and drying to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, dispersing the sulfonic acid-boric acid double-modified montmorillonite powder in deionized water, ultrasonicating, adding the gradient branched polymer solution, stirring, adjusting the pH value of the system to 8.3-8.7, and standing to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and sieve it to obtain a new thickener for oil well fracturing.
[0009] Preferably, in step S1, the weight ratio of hydroxyethyl methacrylate, phenylboric acid and ethanol is 100-140:70-80:480-520.
[0010] Preferably, in step S1, hydroxyethyl methacrylate and phenylboric acid are added to ethanol and stirred at a constant temperature of 77-79° C., a stirring time of 5-6 h, and a stirring speed of 200-300 rpm.
[0011] Preferably, in step S1, distillation is performed under reduced pressure, with a distillation temperature of 55-65° C. and a pressure of 0.08-0.12 MPa.
[0012] Preferably, in step S2, the weight ratio of four-arm polyethylene glycol chain transfer agent, modified hydroxyethyl methacrylate, acrylamide, hydroxyethyl methacrylate, deionized water, ammonium persulfate and hydroquinone is 22-26: 100-140: 340-380: 2-5: 900-1100: 4-8: 0.3-0.7.
[0013] Preferably, in step S2, the weight ratios of the three additions of ammonium persulfate are 2-4:1-2:1-2, respectively.
[0014] Preferably, in step S2, filtering is performed through a 180-220 mesh filter.
[0015] Preferably, in step S3, the weight ratio of montmorillonite, 3-aminopropyltriethoxysilane, ethanol, sulfosuccinic anhydride and phenylboric acid is 55-65:10-20:280-320:9-10:5-7.
[0016] Preferably, in step S3, montmorillonite and 3-aminopropyltriethoxysilane are added to ethanol and then stirred at a constant temperature of 79-81° C., a stirring time of 3-4 h, and a stirring speed of 350-450 rpm.
[0017] Preferably, in step S3, after adding sulfosuccinic anhydride, constant temperature stirring is performed, the constant temperature is 55-65° C., the stirring time is 1.5-2.5 h, and the stirring speed is 200-300 rpm.
[0018] Preferably, in step S3, a sodium hydroxide solution with a mass fraction of 0.1 mol / L is used to adjust the pH value of the system to 7.2-7.8.
[0019] Preferably, in step S3, after adding phenylboric acid, constant temperature stirring is performed, the constant temperature is 55-65° C., the stirring time is 1.5-2.5 h, and the stirring speed is 200-300 rpm.
[0020] Preferably, in step S3, the drying is carried out at 55-65°C.
[0021] Preferably, in step S4, the weight ratio of the sulfonic acid-boric acid double-modified montmorillonite powder, deionized water, and gradient branched polymer solution is 55-65:180-220:1200-1400.
[0022] Preferably, in step S4, ultrasound is used, the ultrasound treatment time is 20-40 min, and the ultrasound frequency is 40-60 kHz.
[0023] Preferably, in step S4, after adding the gradient branched polymer solution, constant temperature stirring is performed, the constant temperature is 55-65° C., the stirring time is 5-6 h, and the stirring speed is 200-300 rpm.
[0024] Preferably, in step S4, a sodium hydroxide solution with a mass fraction of 0.1 mol / L is used to adjust the pH value of the system to 8.3-8.7.
[0025] Preferably, in step S4, the mixture is allowed to stand at a temperature of 55-65° C. for a time of 10-14 h.
[0026] Preferably, in step S5, spray drying is performed with a feed rate of 20 mL / min, an inlet temperature of 170° C., and an outlet temperature of 80° C.
[0027] Preferably, in step S5, the product is sieved through a 200-mesh sieve.
[0028] A novel thickener for oil well fracturing is prepared by using any of the above-mentioned methods for preparing the novel thickener for oil well fracturing.
[0029] Beneficial effects: The present invention has developed a new type of thickener that adapts to the high-temperature and high-salt oil well environment through molecular-level functional synergy and structural design, and systematically solves the problems of traditional thickeners being easy to lose viscosity due to salt precipitation in high-mineralization formations, easy to fail in high-temperature environments, and difficult to repair shear damage. Compared with the existing technology that relies on a single anti-salt group or simple physical blending modification, this solution starts from the molecular structure, through the monomer dynamic bond design, gradient polymerization function distribution and montmorillonite interface synergistic enhancement, forming a "salt resistance-temperature resistance-self-repairing" performance closed loop, which significantly improves the comprehensive performance of the thickener.
[0030] Specifically, firstly, through the directional modification of phenylboronic acid and hydroxyethyl methacrylate, the dynamic borate ester bond introduced into the monomer molecule can be reversibly broken and reorganized at high temperature, effectively repairing the network damage caused by shear or thermal degradation, breaking through the limitations of irreversible failure of traditional static cross-linked networks. Secondly, a four-arm initiator is used to guide the gradient polymerization of acrylamide and functional monomers, and the growth direction of the molecular chain is controlled in stages to form a functional partition structure of "dynamic repair core-transition layer-thickening shell", so that the dynamic bonds are concentrated in the inner core to achieve long-term self-repair, and the pure acrylamide chain segment of the outer shell quickly absorbs water and thickens, taking into account the initial viscosity establishment and long-term stability. Furthermore, by performing bifunctional modification on the surface of montmorillonite, the sulfonic acid group shields the attack of salt ions through strong charge repulsion, solving the problem of salt precipitation and viscosity loss in high-mineralization strata; the boric acid group, as a dynamic anchor point, forms a reversible network with the polymer hydroxyl group, combined with the physical enhancement of montmorillonite nanosheets, significantly improving the shear resistance and temperature resistance limit.
[0031] The present invention achieves performance upgrade through the synergy of monomer-polymer-interface enhancement, the dynamic bond design lays the foundation for self-repair, the gradient polymerization optimizes the function distribution, and the montmorillonite double modification simultaneously undertakes salt resistance and interface cross-linking. In practical applications, the thickener quickly thickens and carries the proppant during the low-temperature pumping stage, and the core dynamic bond triggers self-repair after entering the high-temperature formation. The montmorillonite enhances the network stability, and the dynamic network partially dissociates during the backflow to reduce the viscosity, providing reliable technical support for the development of deep shale gas and tight oil. DETAILED DESCRIPTION
[0032] The present invention will be further explained below in conjunction with specific embodiments.
[0033] Example 1 A method for preparing a novel thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 100 g of hydroxyethyl methacrylate and 70 g of phenylboric acid to 480 g of ethanol, seal, stir at 77°C for 5 h at a stirring speed of 200 rpm, cool to room temperature, and distill under reduced pressure at 55°C and 0.08 MPa to obtain modified hydroxyethyl methacrylate (hydroxyl group of hydroxyethyl methacrylate is esterified with phenylboric acid to form a dynamic borate ester bond); S2, dissolving 22g of four-arm polyethylene glycol chain transfer agent, 100g of modified hydroxyethyl methacrylate, 340g of acrylamide, and 2g of hydroxyethyl methacrylate in 900g of deionized water, stirring at a constant temperature of 48°C for 1.8h, stirring at a speed of 480rpm, adding 2g of ammonium persulfate, stirring at a constant temperature of 58°C for 2.8h, stirring at a speed of 280rpm, adding 1g of ammonium persulfate, stirring at a constant temperature of 68°C for 0.8h, stirring at a speed of 180rpm, adding 1g of ammonium persulfate, adding 0.3g of hydroquinone, cooling, and filtering through a 180-mesh filter to obtain a gradient branched polymer solution (the four-arm initiator regulates the polymerization of acrylamide and modified hydroxyethyl methacrylate in stages to form functionalized molecular chains); S3, 55g montmorillonite, 10g 3-Aminopropyltriethoxysilane was added to 280g of ethanol, sealed, and stirred at a constant temperature of 79°C for 3h at a stirring speed of 350rpm (3-aminopropyltriethoxysilane condensed with the silanol group on the surface of montmorillonite to introduce amino groups), 9g of sulfosuccinic anhydride was added, and stirred at a constant temperature of 55°C for 1.5h at a stirring speed of 200rpm (sulfosuccinic anhydride reacted with amino groups to graft sulfonic acid groups to enhance the synergistic effect of salt resistance), the pH value of the system was adjusted to 7.2 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, 5g of phenylboric acid was added, and stirred at a constant temperature of 55°C for 1.5h at a stirring speed of 200rpm (phenylboric acid reacted with the hydroxyl group on the surface of montmorillonite to fix the boric acid group as a dynamic cross-linking anchor point), centrifuged, washed, and dried at 55°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder (montmorillonite hydroxyl groups reacted with 3-aminopropyltriethoxysilane amino groups, sulfosuccinic anhydride, and phenylboric acid); S4, disperse 55g of sulfonic acid-boric acid double-modified montmorillonite powder in 180g of deionized water, ultrasonically treat for 20min, the ultrasonic frequency is 40kHz, add 1200g of gradient branched polymer solution, stir at 55°C for 5h, the stirring speed is 200rpm, adjust the pH value of the system to 8.3 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and keep it at 55°C for 10h (under pH 8.5, the boric acid group of the sulfonic acid-boric acid double-modified montmorillonite powder forms a reversible borate ester bond with the hydroxyl group of the polymer, and the dynamic bond breaks and reorganizes at high temperature to give it self-healing ability), and obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 15 mL / min, the inlet temperature to 165° C., the outlet temperature to 75° C., and pass it through a 180-mesh sieve to obtain a new thickener for oil well fracturing.
[0034] Example 2 A method for preparing a novel thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 140 g of hydroxyethyl methacrylate and 80 g of phenylboric acid to 520 g of ethanol, seal, stir at 79 ° C for 6 h, stirring speed is 300 rpm, cool to room temperature, and distill under reduced pressure at 65 ° C and 0.12 MPa to obtain modified hydroxyethyl methacrylate; S2, dissolving 26g of four-arm polyethylene glycol chain transfer agent, 140g of modified hydroxyethyl methacrylate, 380g of acrylamide, and 5g of hydroxyethyl methacrylate in 1100g of deionized water, stirring at a constant temperature of 52°C for 2.2h, stirring at a speed of 520rpm, adding 4g of ammonium persulfate, stirring at a constant temperature of 62°C for 3.2h, stirring at a speed of 320rpm, adding 2g of ammonium persulfate, stirring at a constant temperature of 72°C for 1.2h, stirring at a speed of 220rpm, adding 2g of ammonium persulfate, adding 0.7g of hydroquinone, cooling, and filtering through a 220-mesh filter to obtain a gradient branched polymer solution; S3, add 65g montmorillonite and 20g 3-aminopropyltriethoxysilane to 320g ethanol, seal, stir at 81°C for 4h, stirring at 450rpm, add 10g sulfosuccinic anhydride, stir at 65°C for 2.5h, stirring at 300rpm, adjust the pH value of the system to 7.8 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, add 7g phenylboric acid, stir at 65°C for 2.5h, stirring at 300rpm, centrifuge, wash, and dry at 65°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, disperse 65g of sulfonic acid-boric acid double-modified montmorillonite powder in 220g of deionized water, ultrasonically treat for 40min, the ultrasonic frequency is 60kHz, add 1400g of gradient branched polymer solution, stir at 65°C for 6h, the stirring speed is 300rpm, adjust the pH value of the system to 8.7 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and stand at 65°C for 14h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 25 mL / min, the inlet temperature to 175° C., the outlet temperature to 85° C., and pass it through a 220-mesh sieve to obtain a new thickener for oil well fracturing.
[0035] Example 3 A method for preparing a novel thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 120 g of hydroxyethyl methacrylate and 75 g of phenylboric acid to 500 g of ethanol, seal, stir at 78 ° C for 5.5 h, stirring speed is 250 rpm, cool to room temperature, and distill under reduced pressure at 60 ° C and 0.1 MPa to obtain modified hydroxyethyl methacrylate; S2, 24g of four-arm polyethylene glycol chain transfer agent, 120g of modified hydroxyethyl methacrylate, 360g of acrylamide, and 3.5g of hydroxyethyl methacrylate were dissolved in 1000g of deionized water, stirred at a constant temperature of 50°C for 2h, with a stirring speed of 500rpm, 3g of ammonium persulfate was added, stirred at a constant temperature of 60°C for 3h, with a stirring speed of 300rpm, 1.5g of ammonium persulfate was added, stirred at a constant temperature of 70°C for 1h, with a stirring speed of 200rpm, 1.5g of ammonium persulfate was added, 0.5g of hydroquinone was added, cooled, and filtered through a 200-mesh filter to obtain a gradient branched polymer solution; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring at 400rpm, add 9.5g sulfosuccinic anhydride, stir at 60°C for 2h, stirring at 250rpm, adjust the pH value of the system to 7.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, add 6g phenylboric acid, stir at 60°C for 2h, stirring at 250rpm, centrifuge, wash, and dry at 60°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, disperse 60g of sulfonic acid-boric acid double-modified montmorillonite powder in 200g of deionized water, ultrasonically treat for 30min, the ultrasonic frequency is 50kHz, add 1300g of gradient branched polymer solution, stir at 60°C for 5.5h, the stirring speed is 250rpm, adjust the pH value of the system to 8.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and stand at 60°C for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a new thickener for oil well fracturing.
[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that in step S1, phenylboric acid is not added, resulting in the lack of dynamic borate ester bonds, the inability to self-repair at high temperature, and the irreversible breakage of the molecular chain.
[0037] A method for preparing a thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, 120 g of hydroxyethyl methacrylate and 9.5 g of sulfosuccinic anhydride were added to 500 g of ethanol, stirred for 2.5 h at a stirring speed of 250 rpm, and distilled under reduced pressure at 60 ° C and 0.1 MPa to obtain a prefabricated material; S2, 24g of four-arm polyethylene glycol chain transfer agent, 120g of preform, 360g of acrylamide, 3.5g of hydroxyethyl methacrylate were dissolved in 1000g of deionized water, stirred at 50°C for 2h, stirring speed was 500rpm, 3g of ammonium persulfate was added, stirred at 60°C for 3h, stirring speed was 300rpm, 1.5g of ammonium persulfate was added, stirred at 70°C for 1h, stirring speed was 200rpm, 1.5g of ammonium persulfate was added, 0.5g of hydroquinone was added, cooled, filtered through a 200-mesh filter, and a gradient branched polymer solution was obtained; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring at 400rpm, add 9.5g sulfosuccinic anhydride, stir at 60°C for 2h, stirring at 250rpm, adjust the pH value of the system to 7.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, add 6g phenylboric acid, stir at 60°C for 2h, stirring at 250rpm, centrifuge, wash, and dry at 60°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, disperse 60g of sulfonic acid-boric acid double-modified montmorillonite powder in 200g of deionized water, ultrasonically treat for 30min, the ultrasonic frequency is 50kHz, add 1300g of gradient branched polymer solution, stir at 60°C for 5.5h, the stirring speed is 250rpm, adjust the pH value of the system to 8.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and stand at 60°C for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a thickener for oil well fracturing.
[0038] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the staged polymerization is cancelled in step S2, and all reactions are performed at 60° C. at one time, resulting in no functional partitioning of the molecular chain and failure of the salt resistance and self-repair synergy.
[0039] A method for preparing a thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 120 g of hydroxyethyl methacrylate and 75 g of phenylboric acid to 500 g of ethanol, seal, stir at 78 ° C for 5.5 h, stirring speed is 250 rpm, cool to room temperature, add 9.5 g of sulfosuccinic anhydride, stir for 2.5 h, stirring speed is 250 rpm, and distill under reduced pressure at 60 ° C and 0.1 MPa to obtain modified hydroxyethyl methacrylate; S2, dissolving 24g of four-arm polyethylene glycol chain transfer agent, 120g of modified hydroxyethyl methacrylate, 360g of acrylamide, and 3.5g of hydroxyethyl methacrylate in 1000g of deionized water, stirring at a constant temperature of 60°C for 6h, stirring at a speed of 300rpm, adding 6g of ammonium persulfate, adding 0.5g of hydroquinone, cooling, and filtering through a 200-mesh filter to obtain a polymer solution; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring at 400rpm, add 9.5g sulfosuccinic anhydride, stir at 60°C for 2h, stirring at 250rpm, adjust the pH value of the system to 7.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, add 6g phenylboric acid, stir at 60°C for 2h, stirring at 250rpm, centrifuge, wash, and dry at 60°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, disperse 60g of sulfonic acid-boric acid double-modified montmorillonite powder in 200g of deionized water, ultrasonically treat for 30min, the ultrasonic frequency is 50kHz, add 1300g of polymer solution, stir at 60℃ for 5.5h, the stirring speed is 250rpm, adjust the pH value of the system to 8.5 with 0.1mol / L sodium hydroxide solution, and keep it at 60℃ for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a thickener for oil well fracturing.
[0040] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that in step S3, sulfosuccinic anhydride is not added, resulting in the montmorillonite having no sulfonic acid group, and the molecular chains aggregate and precipitate due to salt ion attack.
[0041] A method for preparing a thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 120 g of hydroxyethyl methacrylate and 75 g of phenylboric acid to 500 g of ethanol, seal, stir at 78 ° C for 5.5 h, stirring speed is 250 rpm, cool to room temperature, add 9.5 g of sulfosuccinic anhydride, stir for 2.5 h, stirring speed is 250 rpm, and distill under reduced pressure at 60 ° C and 0.1 MPa to obtain modified hydroxyethyl methacrylate; S2, 24g of four-arm polyethylene glycol chain transfer agent, 120g of modified hydroxyethyl methacrylate, 360g of acrylamide, and 3.5g of hydroxyethyl methacrylate were dissolved in 1000g of deionized water, stirred at a constant temperature of 50°C for 2h, with a stirring speed of 500rpm, 3g of ammonium persulfate was added, stirred at a constant temperature of 60°C for 3h, with a stirring speed of 300rpm, 1.5g of ammonium persulfate was added, stirred at a constant temperature of 70°C for 1h, with a stirring speed of 200rpm, 1.5g of ammonium persulfate was added, 0.5g of hydroquinone was added, cooled, and filtered through a 200-mesh filter to obtain a gradient branched polymer solution; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring speed is 400rpm, adjust the pH value of the system to 7.5 with 0.1mol / L sodium hydroxide solution, add 6g phenylboric acid, stir at 60°C for 2h, stirring speed is 250rpm, centrifuge, wash, and dry at 60°C to obtain modified montmorillonite powder; S4, disperse 60g of modified montmorillonite powder in 200g of deionized water, ultrasonically treat for 30min, the ultrasonic frequency is 50kHz, add 1300g of gradient branched polymer solution, stir at 60°C for 5.5h, the stirring speed is 250rpm, adjust the pH value of the system to 8.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and stand at 60°C for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a thickener for oil well fracturing.
[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that in step S3, phenylboric acid is not added, resulting in the montmorillonite having no boric acid group, lack of dynamic crosslinking at the interface, and insufficient shear resistance of physical entanglement.
[0043] A method for preparing a thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 120 g of hydroxyethyl methacrylate and 75 g of phenylboric acid to 500 g of ethanol, seal, stir at 78 ° C for 5.5 h, stirring speed is 250 rpm, cool to room temperature, add 9.5 g of sulfosuccinic anhydride, stir for 2.5 h, stirring speed is 250 rpm, and distill under reduced pressure at 60 ° C and 0.1 MPa to obtain modified hydroxyethyl methacrylate; S2, 24g of four-arm polyethylene glycol chain transfer agent, 120g of modified hydroxyethyl methacrylate, 360g of acrylamide, and 3.5g of hydroxyethyl methacrylate were dissolved in 1000g of deionized water, stirred at a constant temperature of 50°C for 2h, with a stirring speed of 500rpm, 3g of ammonium persulfate was added, stirred at a constant temperature of 60°C for 3h, with a stirring speed of 300rpm, 1.5g of ammonium persulfate was added, stirred at a constant temperature of 70°C for 1h, with a stirring speed of 200rpm, 1.5g of ammonium persulfate was added, 0.5g of hydroquinone was added, cooled, and filtered through a 200-mesh filter to obtain a gradient branched polymer solution; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring speed is 400rpm, add 9.5g sulfosuccinic anhydride, stir at 60°C for 2h, stirring speed is 250rpm, adjust the pH value of the system to 7.5 with 0.1mol / L sodium hydroxide solution, centrifuge, wash, and dry at 60°C to obtain modified montmorillonite powder; S4, disperse 60g of modified montmorillonite powder in 200g of deionized water, ultrasonically treat for 30min, the ultrasonic frequency is 50kHz, add 1300g of gradient branched polymer solution, stir at 60°C for 5.5h, the stirring speed is 250rpm, adjust the pH value of the system to 8.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, and stand at 60°C for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a thickener for oil well fracturing.
[0044] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that in step S4, the pH of the system is not adjusted, resulting in the inability of the boric acid group and the hydroxyl group to form a dynamic bond, and the self-repairing network is incomplete.
[0045] A method for preparing a thickener for oil well fracturing comprises the following steps: S1. Under nitrogen protection, add 120 g of hydroxyethyl methacrylate and 75 g of phenylboric acid to 500 g of ethanol, seal, stir at 78 ° C for 5.5 h, stirring speed is 250 rpm, cool to room temperature, add 9.5 g of sulfosuccinic anhydride, stir for 2.5 h, stirring speed is 250 rpm, and distill under reduced pressure at 60 ° C and 0.1 MPa to obtain modified hydroxyethyl methacrylate; S2, 24g of four-arm polyethylene glycol chain transfer agent, 120g of modified hydroxyethyl methacrylate, 360g of acrylamide, and 3.5g of hydroxyethyl methacrylate were dissolved in 1000g of deionized water, stirred at a constant temperature of 50°C for 2h, with a stirring speed of 500rpm, 3g of ammonium persulfate was added, stirred at a constant temperature of 60°C for 3h, with a stirring speed of 300rpm, 1.5g of ammonium persulfate was added, stirred at a constant temperature of 70°C for 1h, with a stirring speed of 200rpm, 1.5g of ammonium persulfate was added, 0.5g of hydroquinone was added, cooled, and filtered through a 200-mesh filter to obtain a gradient branched polymer solution; S3, add 60g montmorillonite and 15g 3-aminopropyltriethoxysilane to 300g ethanol, seal, stir at 80°C for 3.5h, stirring at 400rpm, add 9.5g sulfosuccinic anhydride, stir at 60°C for 2h, stirring at 250rpm, adjust the pH value of the system to 7.5 with a sodium hydroxide solution with a mass fraction of 0.1mol / L, add 6g phenylboric acid, stir at 60°C for 2h, stirring at 250rpm, centrifuge, wash, and dry at 60°C to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, dispersing 60g of sulfonic acid-boric acid double-modified montmorillonite powder in 200g of deionized water, ultrasonically treating for 30min, the ultrasonic frequency is 50kHz, adding 1300g of gradient branched polymer solution, stirring at a constant temperature of 60°C for 5.5h, the stirring speed is 250rpm, and standing at a constant temperature of 60°C for 12h to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and set the feed rate to 20 mL / min, the inlet temperature to 170° C., the outlet temperature to 80° C., and pass it through a 200-mesh sieve to obtain a thickener for oil well fracturing.
[0046] Performance Testing The thickeners prepared in Examples 1-3 and Comparative Examples 1-5 were added to deionized water at a certain concentration, stirred for 30 minutes until completely dissolved, allowed to stand at 25° C. for 2 hours to eliminate bubbles, and the pH value of the system was adjusted to prepare a sample. The initial viscosity was measured by a Brookfield DV3T viscometer to be V0.
[0047] Salt resistance: According to SY / T 5107-2016 standard, CaCl2 was added, stirred at a constant temperature of 60°C for 4 hours, and the viscosity V1 of the treated sample was measured, and the viscosity retention rate data was recorded. The results are shown in Table 1.
[0048] Calculation formula: Viscosity retention rate (%) 00%.
[0049] Temperature resistance: According to SY / T 5107-2016 standard, use high temperature and high pressure rheometer (Haake MARS 60), set at 150℃, at 170s-1 The sample was tested for 4 hours at the shear rate and the viscosity V2 data was recorded. The results are shown in Table 1.
[0050] Self-healing efficiency: Apply the sample for 1000s -1 Shear for 1 minute, let stand for 10 minutes to recover; repeat 3 times, measure the final viscosity V3, and record the viscosity recovery rate data. The results are shown in Table 1.
[0051] Calculation formula: Viscosity recovery rate (%) = 00%.
[0052] Table 1 Performance test results
[0053] Data Analysis: It can be seen from the data of Examples 1-3 in Table 1 that the new thickener for oil well fracturing prepared by the present invention has heat resistance, salt resistance and self-repairing properties. Specifically, the average viscosity retention rate of the salt resistance test is 90%, and the maximum can reach 90.5%; the average viscosity of the temperature resistance test is 48.2 mPa·s, and the maximum can reach 48.5 mPa·s; the average viscosity recovery rate of the self-repairing efficiency test is 94.6%, and the maximum can reach 95.3%.
[0054] Compared with Example 3, the thickener prepared in Comparative Example 1 is significantly reduced in temperature resistance, self-repairing ability and salt resistance. This is because phenylboric acid is not introduced in step S1, and the dynamic borate ester bond is missing in the functional monomer, and the structure is maintained only by physical entanglement, which makes it impossible for the material to repair network damage through reversible cross-linking at high temperatures, and also causes the viscosity to decay rapidly. Although the sulfonic acid group is still retained on the surface of montmorillonite to provide partial salt resistance, the lack of synergistic effect of dynamic bonds still leads to a decline in overall performance. In practical applications, the thickener is easy to lose viscosity in high-temperature well sections, and cannot maintain sand carrying capacity for a long time. It is also impossible to reduce viscosity through dynamic bond dissociation during flowback, indicating that dynamic bond design is the core foundation of temperature resistance and self-repairing functions.
[0055] Compared with Example 3, the initial thickening speed and long-term stability of Comparative Example 2 are inferior to those of Example 3. This is because the one-time polymerization leads to the random distribution of functional groups, the dynamic bonds and thickening segments are mixed, and the long-term protective effect cannot be concentrated. During actual pumping, the initial viscosity of the liquid is slowly established, and the functional area dispersion at high temperature leads to reduced self-repair efficiency. Gradient polymerization controls the growth direction of the molecular chain in stages to achieve precise functional distribution of dynamic bonds concentrated in the core and thickening segments extending outward. The homogenized structure of Comparative Example 2 proves that functional zoning is a necessary strategy to balance rapid thickening and long-term stability.
[0056] The salt resistance of comparative example 3 is significantly reduced, and the temperature resistance is also weakened. This is because the montmorillonite is not grafted with sulfonic acid groups, so the interfacial synergistic effect cannot be formed, and the nanosheets are prone to agglomeration due to insufficient surface charge, which weakens the physical enhancement effect. In practical applications, the thickener is prone to salt precipitation and viscosity loss in a high-salt environment, proving that montmorillonite sulfonation is the key to salt resistance synergy and dispersion stability.
[0057] The self-healing ability and temperature resistance of comparative example 4 are significantly reduced. This is because montmorillonite is not modified with boric acid groups and cannot be combined with polymers as dynamic anchor points. It only relies on physical entanglement to enhance the network. It lacks the ability to reorganize chemical cross-linking at high temperatures, and the molecular chain is prone to slip and break. In the actual downhole shear environment, the thickener is difficult to maintain stable viscosity, proving that the boric acid-based dynamic anchor point is a necessary design for interface enhancement and self-healing.
[0058] The self-healing efficiency of comparative example 5 is greatly reduced. This is because under neutral conditions, the boric acid group and the hydroxyl group cannot form a dynamic network, and it is difficult to build a stable network by relying solely on physical mixing. The free movement of the molecular chain is intensified at high temperatures, and the viscosity decays rapidly. In practical applications, the thickener cannot trigger the self-healing function in high-temperature well sections, proving that pH control is a necessary condition for the formation of a dynamic cross-linked network.
[0059] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing a novel thickener for oil well fracturing, characterized in that: The steps include: S1. Under nitrogen protection, hydroxyethyl methacrylate and phenylboric acid are added to ethanol, sealed, stirred, cooled, and distilled under reduced pressure to obtain modified hydroxyethyl methacrylate; S2, dissolving a four-arm polyethylene glycol chain transfer agent, modified hydroxyethyl methacrylate, acrylamide, and hydroxyethyl methacrylate in deionized water, stirring at a constant temperature of 48-52° C. for 1.8-2.2 h, with a stirring speed of 480-520 rpm, adding ammonium persulfate, stirring at a constant temperature of 58-62° C. for 2.8-3.2 h, with a stirring speed of 280-320 rpm, adding ammonium persulfate, stirring at a constant temperature of 68-72° C. for 0.8-1.2 h, with a stirring speed of 180-220 rpm, adding ammonium persulfate, adding hydroquinone, cooling, filtering, and obtaining a gradient branched polymer solution; S3, adding montmorillonite and 3-aminopropyltriethoxysilane to ethanol, sealing, stirring, adding sulfosuccinic anhydride, stirring, adjusting the pH value of the system to 7.2-7.8, adding phenylboric acid, stirring, centrifuging, washing, and drying to obtain sulfonic acid-boric acid double-modified montmorillonite powder; S4, dispersing the sulfonic acid-boric acid double-modified montmorillonite powder in deionized water, ultrasonicating, adding the gradient branched polymer solution, stirring, adjusting the pH value of the system to 8.3-8.7, and standing to obtain a colloidal solution; S5. Centrifuge the colloidal solution, spray dry it, and sieve it to obtain a new thickener for oil well fracturing.
2. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S1, the weight ratio of hydroxyethyl methacrylate, phenylboric acid and ethanol is 100-140:70-80:480-520.
3. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S2, the weight ratio of the four-arm polyethylene glycol chain transfer agent, modified hydroxyethyl methacrylate, acrylamide, hydroxyethyl methacrylate, deionized water, ammonium persulfate, and hydroquinone is 22-26: 100-140: 340-380: 2-5: 900-1100: 4-8: 0.3-0.
7.
4. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S2, the weight ratios of the three additions of ammonium persulfate are 2-4:1-2:1-2 respectively.
5. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S3, the weight ratio of montmorillonite, 3-aminopropyltriethoxysilane, ethanol, sulfosuccinic anhydride and phenylboric acid is 55-65:10-20:280-320:9-10:5-7.
6. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S3, a sodium hydroxide solution with a mass fraction of 0.1 mol / L is used to adjust the pH value of the system to 7.2-7.
8.
7. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S4, the weight ratio of the sulfonic acid-boric acid double-modified montmorillonite powder, deionized water, and gradient branched polymer solution is 55-65:180-220:1200-1400.
8. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S4, a sodium hydroxide solution with a mass fraction of 0.1 mol / L is used to adjust the pH value of the system to 8.3-8.
7.
9. The method for preparing the novel thickener for oil well fracturing according to claim 1, characterized in that: In the step S5, spray drying is performed with a feed rate of 20 mL / min, an inlet temperature of 170° C., and an outlet temperature of 80° C.
10. A novel thickener for oil well fracturing, characterized in that: The novel thickener for oil well fracturing is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Acid liquor thickening agent as well as preparation method and application thereof
CN113321764A
Embolization microsphere and gradient cross-linking preparation method
CN114478927A
Self-crosslinking emulsion type fracturing fluid thickening agent and preparation method thereof
CN116751329A
Suspended slickwater anti-drag fracturing fluid and preparation method thereof
CN117659985A
Multi-component copolymerization type salt-resistant, high-temperature-resistant and shear-resistant fracturing thickening agent and preparation method thereof
CN117986454A
Cited By
Profile control agent for shale oil reservoir and preparation method thereof
CN122444929A